La pista de aterrizaje de Gibraltar y la base militar - Marquina Barrio, Antonio (UNISCI Discussion Papers, 2009)
The importance of Gibraltar military base, which was utilized by the Armed Forces of the United Kingdom, increased during the Second World War and during the Cold War. Later on, after the dissolution of the Soviet Union, its military role and objectives were redefined. The military base is still an important asset. Given the unpredictability of many geopolitical changes, as history shows, this importance can not be forgotten. On this perspective, the article shows the profound inconsistencies in the Spanish policies maintained and the different approaches and negotiations for the recuperation of the Gibraltar sovereignty.